2018
DOI: 10.1103/physrevd.97.125002
|View full text |Cite
|
Sign up to set email alerts
|

General no-go theorem for entanglement extraction

Abstract: We study under what circumstances a separable bipartite system A-B can or cannot become entangled through local interactions with a bi-local entangled source S1-S2. We obtain constraints on the general forms of the interaction Hamiltonians coupling A with S1 and B with S2 necessary for A and B to become entangled. We are able to generalize and provide non-perturbative insight on several previous no-go theorems of entanglement harvesting from quantum fields using these general results. We also discuss the role … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 49 publications
(99 reference statements)
4
72
0
Order By: Relevance
“…a single use of the channel can transmit at most one qubit), we thus conclude that in the limit λ φ /σ → ∞, the quantum channel capacity Q(Ξ) approaches its maximum value of 1. In other words, we have verified, without the use of any approximations, that the field-mediated quantum channel from Alice to Bob is indeed a perfect quantum channel if the conditions (35) and (36) are satisfied.…”
Section: A Gaussian Detector Smearingmentioning
confidence: 69%
See 1 more Smart Citation
“…a single use of the channel can transmit at most one qubit), we thus conclude that in the limit λ φ /σ → ∞, the quantum channel capacity Q(Ξ) approaches its maximum value of 1. In other words, we have verified, without the use of any approximations, that the field-mediated quantum channel from Alice to Bob is indeed a perfect quantum channel if the conditions (35) and (36) are satisfied.…”
Section: A Gaussian Detector Smearingmentioning
confidence: 69%
“…Additionally, in order for the channel to succeed, the conditions (35) and (36) on the coupling strengths λ φ and λ π must be satisfied. Physically, Eq.…”
Section: Decoding a Qubit Out Of A Fieldmentioning
confidence: 99%
“…Every Hamiltonian gives rise to a unique ground state, but for each state there are plenty of Hamiltonians that share the same ground state. This redundancy is visible in (31) where rescaling h ab with an overall factor (or individually in each frequency sector) leaves G ab unchanged.…”
Section: • Computation Of G Abmentioning
confidence: 99%
“…With this ultimate motivation in mind, it has been shown that a non-zero detector energy gap is crucial in protecting an entanglement harvesting UDW pair against fluctuation induced, entanglement harming, local noise [32,33]. Furthermore, for harmonic oscillator detectors, this noise has been found to increase with field temperature, leading to detrimental effects on the amount of entanglement harvested [18] by oscillator pairs.…”
Section: Introductionmentioning
confidence: 99%